The Controversies over the Term “Empowerment” in the Implementation of Sustainable Development and the Case of Turkey - Eylem Özkaya Lassalle; Selcan Serdaroğlu Polatay (Alternatif Politika)
Sustainable development, being at the centre of today’s global and local policies, has led to discussions about its broad content and applicability since the 1980s. In particular, the most emphasized issues have been prioritizing the economic dimension of sustainable development and understanding the environment as the optimal use of natural capital. However, as was underlined at the World Sustainable Development Summit held in 2002, a social dimension also needs to be taken into account. This study adopts a qualitative approach to explore definitions and dimensions of sustainable development and empowerment to understand how their enlarged content affects their application. The dynamic range of empowerment presented as a critical strategy for implementing the social dimension of sustainable development, the ambiguities related to the meaning of the concepts, and the discourses transmitted from the global to the local level are being investigated through the Turkish case. To explore different definitions of sustainable development and empowerment, the qualitative analysis software Atlas.ti was used. The research sample consists of ten documents on international cooperation initiatives and three Turkish documents on implementing these initiatives. The international and Turkish texts show the fluctuations of empowerment between raising human welfare and increasing production. Thus, the concept of empowerment seems to reflect the contradictions of sustainable development semantically and by the nature of the discourse used.